Bierzmowanie - sakrament chrześcijańskiej dojrzałości, czy pożegnania z Kościołem? - Janczewski, Zbigniew (Prawo Kanoniczne, 2008)
In the beginning of the Church the confirmation was one – same ceremony with the baptism and the Eucharist. It was the rite of come in the Church. Sometimes the confirmation was received whole families, with their children. In the middle century in the Roman Catholic Church those sacrament was giving to the children in “perfectae aetatis” who was 7 year old. In the XX century in Poland the age of confirmation was near 10 year old. After II Vatican Council the Episcopal Conference has decided on a different age. In Poland those age is 15-16 year old. But some of bishops would like to change this age to higher, because (like some people think) a young people must to be more maturity to received the confirmation. Now some of youth after the confirmation finish their religions education in the school, and leave the Church. Author of article think, that they need the grace of sacrament of confirmation in the age more early (before attain age of manhood and womanhood), to help them to keep their faith.